Stability analysis of prey predator model Holling type II with infected prey. (May 2020) - Latipah, K; Putri, A R; Syafwan, M
Abstract: We describe a prey-predator model with infected prey. The model using Holling response function of type II is a nonlinear system of ordinary differential equations consisting of two distinct population. Critical points of the model was determined and stability of the system was analyzed by eigenvalues of Jacobian matrix. The behaviour of the dynamical system was analyzed through this stability. Furthermore, threshold number determining the system is free of disease or infected was computed. Numerical solutions are presented on phase plane to confirm the analytical solutions.